Evaluation of the Role of Renewables Consumption on Economic Growth of the U.S. Regions - Bekareva, Svetlana V.; Meltenisova, Ekaterina N.; Gsysa, J. G. Abo (International Journal of Energy Economics and Policy, 2017)
The article is devoted to a modern situation in the U.S. electricity analysis per state, where renewable energy consumption has grown drastically since the early 2000s. The article estimates electricity restructuring results and their influence on the modern state of this branch of industry. We attempted to assess the influence of various factors involved in the economic growth of the U.S. per state using the methods of cluster and panel data analysis. The numerical data collected refer to the period of 2000–2014. We prove the significance of the renewables share in the economic growth of particular states and the U.S. as a nation. Keywords: renewables, electricity restructuring, economic growth JEL Classifications: O18, O51